Electronic structure and x-ray magnetic circular dichroism in the Heusler alloy Co₂FeSi - Antonov, V.N.; Kukusta, D.A.; Shpak, A.P.; Yaresko, A.N. (Condensed Matter Physics, 2008)
The electronic structure and x-ray magnetic circular dichroism (XMCD) spectra of the Heusler alloy Co₂FeSi were investigated theoretically from first principles, using the fully relativistic Dirac linear MT-orbital (LMTO) band structure method. Densities of valence states, orbital and spin magnetic moments as well as polarization of the electronic states at the Fermi level are analyzed and discussed. The origin of the XMCD spectra in the Co₂FeSi compound is examined. The calculated results are compared with available experimental data.